Geophysics of pedosphere in Kyiv University - Sukhorada, А.; Menshov, О.; Bondar, К.; Kruglov, O.; Khomenko, R.; Popov, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The development of studies of geophysics of pedosphere in Taras Shevchenko National University of Kyiv over the past thirty years is considered. The pedosphere is a unique and extremely informative object for the geophysical research. The physical and chemical properties of the objects within the pedosphere are related to the mineral deposits, soil science processes, anthropogenic influence during agricultural production, environmental pollution, paleogeographic processes, the history of human development as an archaeological heritage. In Ukraine, the study of soil magnetism began in the 90s of the 20th century in Kyiv University on the basis of the Student Design and Research Bureau. At the present moment, the investigation of all the initiated processes continues. The understanding of the physical foundations of the method is essential. The magnetic mineralogy of soils is investigated depending on the conditions of formation or introduction: pedogenesis, technogenesis, influence of hydrocarbons, etc. The new data at the same time verify the already existing theory, as well as deepen the not yet known aspects of the study of the pedosphere, raise new challenges to researchers. Analyzes are carried out both at the macro level within agricultural fields, urban agglomerations, oil and gas-bearing regions, and at the micro level for the smallest soil aggregates (pedon), magnetic minerals, magnetoactive domains, etc. The results of magnetic, magnetometric, electrometric and ground-penetrating radar studies in various spheres of the national economy are given.
Keywords: soil; pedosphere; geophysics; magnetic susceptibility; magnetic survey; electrical methods